The trouble with take-up - Karina Doorley; Theano Kakoulidou (The Economic and Social Research Institute (ESRI), 2023)
Take-up of social welfare is key to its success in alleviating poverty. For a variety of reasons, including stigma, transaction costs and information asymmetry, take-up of welfare benefits is imperfect. This research note discusses the issue of take-up of social welfare and its measurement. We explore the difficulties of estimating welfare take-up, using the example of the Irish Working Family Payment (WFP) and two microsimulation models. We show how estimates of take-up can vary depending on the dataset used for simulation. We then estimate take-up of the WFP, updating the most recent estimate from 2005. Lastly, we discuss policy lessons.
Keywords: 330